The role of the sentinel lymph node (SLN) in gynaecological malignancies – is it time to change the management methods? - Paplicki, Adam; Dańska-Bidzińska, Anna; Sobiczewski, Piotr; Bidziński, Mariusz (Menopause Review/Przegląd Menopauzalny, 2011)
The general application of the sentinel lymph node (SLN) concept in the treatment of gynaecological malignancies can decrease the scope of the surgical procedures as well as reduce the postoperative morbidity or even can lead to the replacement of surgical procedures by alternative treatment.